Estimation of Plastic Tiles Tensile Strength - Sahat, Suhaila; Ahmad Hashim, Ahmad Alif Aiman; Nasrudin, Muhammad Amirul Haqim; Azhar, Anas Akmal (Multidisciplinary Applied Research and Innovation, 2021)
Plastic is mainly used for our daily life. Due to their low cost, ease of manufacture, they are mostly used for packaging, furniture and toys. It is more than a century since plastic was invented and nowadays, plastic waste is one of the causes sources of pollution. Therefore, countries all over the world took wise decision in planning for sustainable environment such as 3R campaign to reduce, reuse and recycle. In our project we recycle plastic bag and make it as a tile. Tile is a thin object usually square or rectangular in shape. The objective of this project is to determine tensile strength of plastic tiles to estimate percentage of recycle plastic bag in producing plastic tile. This research used 100 % plastic bag as main material in the tile. There is no other additional material added. This plastic tile is made by heating process using oven heater at 220 ℃ and then it is compressed by cool press machine to shape it. We used 60 pieces plastic bags to fabricate a tile. However, the estimation of plastic bags used to fabricate a thousand of tiles is 60,000 pieces. The data and result collected for this project were satisfying because it can sustain load up to 1.5 kN for one pieces of tile compared with standard tile the load is 1.1kN(250pound). From the result it ishighly recommend that this plastic tile is suitable to be use for construction industry.